2009
DOI: 10.1177/0269216309105726
|View full text |Cite
|
Sign up to set email alerts
|

Improving training in spiritual care: a qualitative study exploring patient perceptions of professional educational requirements

Abstract: Healthcare professionals express difficulties in delivering spiritual care, despite it being a core component of palliative care national policies. The patient perspective on professional training to address difficulties has not previously been sought. The aim of this study is to describe patient suggestions for development of training to deliver spiritual care. Qualitative semi-structured in-depth 'palliative patient' interviews (n = 20) were analysed thematically. Training suggestions encompassed practical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
41
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 30 publications
0
41
0
2
Order By: Relevance
“…In religion there is a God and individuals who share the same beliefs, worshipful acts within some kind of social institution. Existentialism comprises the questions of life, the basic condition of being human, where freedom, existential isolation, meaning and death become central issues (Strang, 2006;Aldridge, 2000;Yalom, 1980) Patients expect healthcare staff to be comfortable discussing existential issues with them and that staff address these concerns sensitively (Yardley et al, 2009). In interviews with patients receiving palliative care and palliative healthcare staff about the optimal content of end-of-life discussions, existential issues were found to be important to both groups, although healthcare staff did not feel that it was their role to discuss such issues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In religion there is a God and individuals who share the same beliefs, worshipful acts within some kind of social institution. Existentialism comprises the questions of life, the basic condition of being human, where freedom, existential isolation, meaning and death become central issues (Strang, 2006;Aldridge, 2000;Yalom, 1980) Patients expect healthcare staff to be comfortable discussing existential issues with them and that staff address these concerns sensitively (Yardley et al, 2009). In interviews with patients receiving palliative care and palliative healthcare staff about the optimal content of end-of-life discussions, existential issues were found to be important to both groups, although healthcare staff did not feel that it was their role to discuss such issues.…”
Section: Introductionmentioning
confidence: 99%
“…Symptom distress is complex and it is crucial that healthcare staff, when encountering dying patients, understands and recognize the most vulnerable persons (Chochinov et al, 2009). Many patients with cancer have a desire to share their existential concerns with healthcare professionals (Yardley et al, 2009), and professionals are aware of this need (Browall et al, 2010) but the question is whether they are able to identify specific opportunities to participate in conversations about patients' existential needs.…”
Section: Introductionmentioning
confidence: 99%
“…In a study that explored hospice patients' suggestions regarding professionals' spiritual training, it was found that patients expect that healthcare professionals feel comfortable when discussing existential issues with patients and address these concerns sensitively (5). Affirmative relationships enable patients to identify their inner resources.…”
Section: Introductionmentioning
confidence: 99%
“…Astrow et al (2007) observed that clients who reported their spiritual needs were not adequately addressed reported significantly lower levels of satisfaction with their medical care. Palliative care patients have stated that they would rather be offered spiritual care and be free to refuse it rather than it to not be offered at all (Yardley, Walshe & Parr 2009). In a study of parents of children who have died at a pediatric hospital, parents indicated that spiritual care is very important in the care of a dying child (Weidner, Cameron, Lee, McBride, & Mathias 2011).…”
mentioning
confidence: 99%